Seasonal, interannual and decal variability of Tropospheric Ozone in the North Atlantic: Comparison of UM-UKCA and remote sensing observations for 2005–2018 - Russo, Maria R.; Kerridge, Brian J.; Abraham, Nathan L.; Keeble, James; Latter, Barry G.; Siddans, Richard; Weber, James; Griffiths, Paul T.; Pyle, John A.; Archibald, Alexander T. (2022)
Tropospheric ozone is an important component of the Earth System as it can affect both climate and air quality. In this work we use observed tropospheric column ozone derived from the Ozone Monitoring Instrument (OMI) and Microwave Limb Sounder (MLS) OMI-MLS, in addition to OMI ozone retrieved in discrete vertical layers, and compare it to tropospheric ozone from UM-UKCA simulations (which utilise the Unified Model, UM, coupled to UK Chemistry and Aerosol, UKCA). Our aim is to investigate recent changes (2005–2018) in tropospheric ozone in the North Atlantic region, and specifically its seasonal, interannual and decadal variability and to understand what factors are driving such changes. Through sensitivity experiments, timeseries correlation and comparison with the LIS-OTD lightning flash dataset, the model positive bias in the Tropics is attributed to shortcomings in the convection and lightning parameterisations. Use of OMI data, for which vertical averaging kernels and a priori information are available, suggests that the model negative bias at mid latitudes relative to OMI-MLS tropospheric column could be the result of vertical sampling. Ozone in the North Atlantic peaks in spring and early summer, with generally good agreement between the modelled and observed seasonal cycle. Recent trends in tropospheric ozone were investigated and the discrepancy between model and observations was linked to possible differences in lower stratospheric ozone trends and associated stratosphere to troposphere transport. Modelled tropospheric ozone interannual variability (IAV) is driven by IAV of tropical emissions of NOx from lightning and IAV of ozone transport from the stratosphere; however, the modelled and observed IAV differ. To understand the IAV discrepancy we investigated how modelled ozone and its drivers respond to large scale modes of variability. Using OMI height-resolved data and model idealised tracers, we were able to identify stratospheric transport of ozone into the troposphere as the main driver of the dynamical response of North Atlantic ozone to the Arctic Oscillation (AO) and the North Atlantic Oscillation (NAO). Finally, the ozone response to El Nino Southern Oscillation (ENSO) and its impact on observed and modelled north Atlantic ozone variability was analysed.